Post-partum milk progesterone profiles in SahiwalxFriesian cows on different energy intake. - Adam, A.; Tan, H. S.; Jamak, M. Eusof (1984)
Progesterone (P4) concentration in 21 SahiwalxFriesian cows kept on three energy levels (n=7) were determined thrice weekly for 120 days after first calving using a simple direct radioimmunoassay in fat-free milk. Based on post-partum P4 profiles, resumption of ovarian activity (Mean ± S.D.) commenced at 32.9 ± 19.2, 22.4 ± 14.3 and 25.6 ± 8.8 days post-partum for low, medium and high energy groups, respectively. Using P4 levels of ≥ 1 ng/ml as a criterion for corpus luteum activity, first ovulation occured at 37.7 ± 18.0, 26.6 ± 15.7 and 25.3 ± 8.3 days post-partum, respectively. Although intervals to resumption of ovarian activity and to first ovulation were longer in the low energy group, these differences were not significant (P < 0.05). First observed oestrus was noted at 28.0 ± 21.6, 32.7 ± 9.8 and 25.4 ± 6.0 days post-partum for low, medium and high energy groups, with 13.6, 29.6 and 14.3% incidence of undetected oestrus, respectively. From P4 profiles, mean cycle length before conception of the three groups were 19.9 ± 4.1, 19.3 ± 3.8 and 20.9 ± 3.6 days, while the intervals from calving to conception were 74.3 ± 14.9, 79.1 ± 17.3 and 88.3 ± 30.4 days, respectively. A higher incidence of repeat breeding was observed in the high energy group although mean intervals to conception were not significantly different.